4CPS-162 Pharmaceutical interventions in drugs provided to the outpatient hospital pharmacy. (24th March 2020) - Brito, A; Fernandes, A; Lourenço, L; Domingos, S; Alcobia, A
Abstract : Background and importance: Pharmacists are responsible for outpatient drug distribution. The aim is not just to provide the medication but also to prevent, acknowledge and resolve medication related problems (MRP). The value of pharmaceutical interventions (PIs) is reflected in adherence, healthcare education and promotion of quality of life in patient. Aim and objectives: To assess and characterise PIs performed in outpatients, their caregivers and other healthcare professionals. Material and methods: This was a retrospective longitudinal study conducted in all patients treated in the outpatient hospital pharmacy between November 2018 and August 2019. PIs were recorded and classified according to type, reason, time and outcome of the intervention. Results: During the study period, 663 PIs (n=38057 patients) were recorded. The specialties with the largest number of interventions were infectious disease (41.9%), oncology (26.5%) and gastroenterology (14.6%). The PI targets were patients (62.7%), caregivers (12.2%), physicians (22.9%) and other healthcare professionals (2.2%). We highlighted PIs related to therapeutic education (37.1%), verification/reinforcement of adherence (21.1%) and pharmaceutical consultation (7.4%). The most relevant reasons for PIs were new patient/new drug (44.5%), poor adherence (21.5%), incorrect intake/insufficient therapy knowledge (4.9%), wrong drug prescribed (4.1%) and suspected adverse drug reaction (1.1%). A total of 67.3% of PIs took 5–15 min and 19.1% >15 min. The acceptance rate of pharmaceutical recommendations was 92.9%. Conclusion and relevance: Pharmacists are essential when dispensing drugs, not only for providing information and therapeutic teaching, but also to actively detect MRP. Due to the high number of daily consultations performed (about 200 patients/day) and lack of human resources, it is likely that PIs are underreported. Communication between different health professionals is essential in the resolution of MRP, contributing to safety improvements and therapy optimisations. PIs had a high acceptance rate which demonstrates the importance and recognition of the pharmacist's role. References and/or acknowledgements: 1. Boorman S, et al. Another way forward for pharmaceutical care: a team-based clinical pharmacy service. Pharm J 2000;264. No conflict of interest.